Brown tumor due to primary hyperparathyroidism in a familial case: a case report - Zongping Diao; Jianquan Zhang; Jiaqi Zhao; Weihu Sun; Zhengguo Pu (BMC Endocrine Disorders, 2023)
Abstract Background Primary hyperparathyroidism (PHPT) is an uncommon disorder characterised by hypercalcemia with an increased parathyroid hormone level. We reported a PHPT familial case with two subjects, a father and a daughter, and both of them had suffered from the brown tumor. Case presentation The proband, a 43-year-old patient, developed parathyroid adenomas at the age of 15; a histologically confirmed right parathyroid adenoma was removed by parathyroidectomy; and after six months follow-up, the serum calcium level was normalised. At the age of thirty-three, a CT scan of his head and neck revealed a mass in the right maxilla, as well as PHPT (i.e., left inferior parathyroid adenoma). Then, he underwent a biopsy of an exophytic lesion in the right maxilla and was diagnosed by pathology as a brown tumor, with the serum calcium and PTH levels at 2.78 mmol/L and 221 pg/mL, respectively. Subsequently, the patient took a left inferior parathyroid microwave ablation with ultrasound guidance. After three months of follow-up, the serum calcium and PTH levels returned to normal, and the brown tumor was resolved. After three years, it mineralised as revealed in a CT scan. By the time he was 43 years old, during the 28-year follow-up period, the serum calcium and PTH levels were still within the normal range, and there was no discomfort reported. He has consistently taken calcium supplements throughout the 28 years. Since the initial diagnosis, his blood indicators of kidney function have been normal, and ultrasound showed renal calculus in the right kidney and a normal left kidney. The proband’s daughter, a 15-year-old girl, experienced left upper extremity pain for ten months. CT scan revealed a mass in the distal left radius, and a giant cell tumor was suspected. A surgical internal fixation was performed, and the pathology showed a brown tumor. Laboratory tests revealed a serum parathyroid hormone (PTH) level of 1554pg/mL, calcium level of 3.14 mmol/L, phosphorus level of 0.72 mmol/L, and alkaline phosphatase level of 1892 U/L. Given the osteitic changes and elevated levels of calcium and PTH, ultrasonography was performed, after which a mass was detected measuring 19 × 9 × 7 mm mixed with solid components and cystic fluid in the right thyroid gland. The results of 99mTc-MIBI scintigraphy confirmed the abnormal accumulation of 99mTc-MIBI in the right thyroid gland but not seen in the bilateral parathyroid glands. The patient underwent thyroidectomy, and the postoperative pathology report indicated an intra-thyroid ectopic parathyroid adenoma. The serum calcium and PTH levels became normal at 4 h after surgery. One to three months after operation, the serum calcium level was low, while the serum PTH level was high. Then, the patient was advised to take calcium supplements. Until the sixth month after the operation, the serum calcium level and serum PTH level returned to normal, and the bone pain was relieved. The patient’s blood tests for kidney function remained normal. There was no evidence of bilateral kidney disease (such as nephrolithiasis or nephrocalcinosis) detected by ultrasound scan. There were several similarities in the state of illness between these two subjects. Both the father and the daughter developed parathyroid adenomas at the age of 15, and there was no lesion in other endocrine glands. And genetic testing revealed mutations in the CDC73 genes in both father and daughter. On the other hand, there were also a few differences. The father’s first signs of brown tumor were in the right maxilla, while the daughter’s appeared in the distal left radius. The father presented pathological changes in the left and right parathyroid glands, whereas the daughter presented with an ectopic parathyroid adenoma in the right thyroid gland. Conclusion We report a familial case in which father and daughter were diagnosed to have brown tumors due to parathyroid adenoma and ectopic parathyroid adenoma, and genetic testing revealed CDC73 gene mutations in both. Therefore, in the diagnostic and differential process of young patients having bone disease, clinicians should not only focus on the clinical manifestations of the skeleton, but also implement a comprehensive analysis of systemic symptoms, considering the possibility that the patient has familial PHPT.